Suspension laryngoscopy experiences in a tertiary airway service: A prospective study of 150 procedures. (14th October 2021) - Maughan, Elizabeth F.; Rotman, Anthony; Rouhani, Maral J.; Thong, Gerard; Poncia, James; Myatt, John; Al Yaghchi, Chadwan; Sandhu, Gurpreet
Abstract: Objectives: In most cases, suspension laryngoscopy (SL) is efficient, bloodless and with minimal post‐procedure discomfort. We aimed to identify predictive patient factors for acceptable surgical views at SL as well as quantify our tertiary airway unit's complication rates. Design: Prospective cohort study of 150 consecutive microlaryngoscopy procedures involving SL over an 8‐month period between November 2019 and July 2020. Patients were assessed preoperatively for pre‐existing oral, temporomandibular, dental, pharyngeal or laryngeal pathology, interincisor distance and qualitative gross limitations to neck extension and forward head posture. Intraoperatively, the laryngoscopic view was graded by anaesthetic and surgical teams, and complications were recorded on patient interview in recovery. Setting: Tertiary adult airway service for predominantly benign pathology. Results: Adequate surgical views were obtained in 149/150 procedures. BMI had a weak positive correlation with a more difficult view ( r = .22, p = .008) but did not correlate with a statistically significant increase in any complication. There was a weak negative correlation between age and interincisor gap ( r = −.20, p = .014), and wider mouth opening correlated very weakly with a lower incidence of sore throat ( r = −.19, p = .023). Gross macroglossia showed a significant moderate positive correlation with tongue symptoms ( r = .45, p = 1.611 × 10 −8 ). Conclusion: In the context of an experienced airway unit with a high caseload of predominantly benign pathology, SL is very effective and safe with low associated morbidity and no mortality. The most common complication of SL is temporary sore throat and there remain recognised risks of temporary tongue and dental symptoms.